Ambient Copper Induced Changes in the Respiration and Excretion of the Freshwater Fish, Sarotherodon mossambicus (Trewaves) - T.S, Saravanan; R, Muthuraman; R, Harikrishnan; M. Aneez, Mohamed (Malaysian Journal of Science, 2003)
The freshwater fish, $Sarotherodon$ $mossambicus$, was exposed to a sublethal concentration (1 mg $L^{-1}$) of the heavy metal, copper for three, six, 12, 24 and 48 hours. The rates of oxygen consumption and ammonia excretion were studied during the above periods. In treated fish, the rate of oxygen consumption was significantly (<0.01) increased to 1.9% and 1.5% for three and six hrs and decreased to 2.2%, 2% and 2.2% for 12, 24 and 48 hours of exposure respectively. While the rate of ammonia excretion was significantly(<0.01) increased to 1.8%, 1.8%, 1.7%, 1.6% and 1.9% respectively in treated fish of all periods. The reason for the alteration in the rates of oxygen consumption and ammonia excretion of treated fish is discussed.The freshwater fish, $Sarotherodon$ $mossambicus$, was exposed to a sublethal concentration (1 mg $L^{-1}$) of the heavy metal, copper for three, six, 12, 24 and 48 hours. The rates of oxygen consumption and ammonia excretion were studied during the above periods. In treated fish, the rate of oxygen consumption was significantly (<0.01) increased to 1.9% and 1.5% for three and six hrs and decreased to 2.2%, 2% and 2.2% for 12, 24 and 48 hours of exposure respectively. While the rate of ammonia excretion was significantly(<0.01) increased to 1.8%, 1.8%, 1.7%, 1.6% and 1.9% respectively in treated fish of all periods. The reason for the alteration in the rates of oxygen consumption and ammonia excretion of treated fish is discussed.